HUBUNGAN KEMATANGAN EMOSI DENGAN PENGAMBILAN KEPUTUSAN KARIR PADA PESERTA DIDIK KELAS XI SMA PGRI 2 PADANG - Faregi Permata; Besti Nora Dwi Putri; Rahmawati Wae (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between emotional maturity and career decision-making in grade XI students of SMA PGRI 2 Padang. This study uses a quantitative correlational approach with data analysis techniques using the Pearson Product Moment test through the IBM SPSS program version 26.0. The results showed that the majority of students had emotional maturity in the stable and fairly stable categories (39%), and career decision-making in the good category (65%). The results of the correlation analysis showed a calculated r-value of 0.579 with an r-table of 0.284 at a significance level of 0.05. Because the calculated r-value > r-table, it can be concluded that there is a positive and significant relationship between emotional maturity and career decision-making in students. The correlation coefficient of 0.579 indicates a fairly strong relationship. This means that the more stable the emotional maturity of students, the better their career decision-making. This finding shows the importance of strengthening the emotional aspect in helping students make the right career decisions.